1985
DOI: 10.1063/1.335700
|View full text |Cite
|
Sign up to set email alerts
|

Surface flashover of solid insulators in atmospheric air and in vacuum

Abstract: The surface flashover of Teflon, plexiglass, quartz, Pyrex glass, Macor glass-ceramic, and sapphire solid insulators has been measured in vacuum (∼10−8 Torr, ∼10−6 Pa) and in atmospheric air using dc, ac (60 Hz), and 1.2/50-μsec lightning impulse voltages. The dependence of the flashover voltage on the following parameters is investigated: (1) spacer material, (2) diameter of the spacer, (3) spacer length, (4) number of spacers stacked in series, (5) air pressure in the range 10−6–105 Pa, (6) electrode materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(43 citation statements)
references
References 15 publications
1
41
1
Order By: Relevance
“…In the present study the mean peak HR (during the final 30 s of exercise in the incremental isometric exercise test) was 122.6 ± 19.0 b min -1 . This was similar to a mean peak HR of 125 b min -1 , derived from five previous double-leg isometric exercise studies (Lewis et al 1985;Misner et al 1990;Fujisawa et al 1996;Smolander et al 1998;Wiles et al 2008). The selection of 95% and 75% peak HR was based on pilot work which showed that the minimum %HR peak that could be elicited successfully, when using EMG, was 75%HR peak .…”
Section: Isometric Exercise Training Sessionsmentioning
confidence: 95%
“…In the present study the mean peak HR (during the final 30 s of exercise in the incremental isometric exercise test) was 122.6 ± 19.0 b min -1 . This was similar to a mean peak HR of 125 b min -1 , derived from five previous double-leg isometric exercise studies (Lewis et al 1985;Misner et al 1990;Fujisawa et al 1996;Smolander et al 1998;Wiles et al 2008). The selection of 95% and 75% peak HR was based on pilot work which showed that the minimum %HR peak that could be elicited successfully, when using EMG, was 75%HR peak .…”
Section: Isometric Exercise Training Sessionsmentioning
confidence: 95%
“…Unfortunately, there is only a limited amount of information regarding M cr , c, and v 0 , with measurements ranging over several orders of magnitude for different experimental setups, [26][27][28][29] and A 1 is only known for a handful of common dielectrics. 30 Therefore, we will treat u as a fitting parameter to compare between static and rf measurements and between different fabrication processes.…”
Section: à4mentioning
confidence: 99%
“…We describe its experimental characteristics, together with a simple model, for barium-titanate based MLCs with nickel electrodes. The dependence of flash-over breakdown field E FB on dielectric length L is found to satisfy the Pillai-Hackam Law [8,9] E FB (L) = a L 1/2 . However, other details support the more complex model of Le Gressus et al [10][11][12][13], including the treeing on the insulator surface and parallel fracture lines.…”
Section: Flashovermentioning
confidence: 85%
“…But at much lower voltages, typically 30% of that required for such direct breakdown, flashover or arcing can cause failure. The basic mechanism is that of Pillai and Hackam [8,9], and a more detailed semiconductor-based model is given by Le Gressus' group [11][12][13].…”
Section: Electrical Breakdownmentioning
confidence: 99%